QM/MM Study of the H2 Formation on the Surface of a Water Ice Grain Doped With Formaldehyde: Molecular Dynamics and Reaction Kinetics - Kerkeni, Boutheïna; Boukallaba, Malek; Hechmi, Mariem; Duflot, Denis; Toubin, Céline (Frontiers in Astronomy and Space Sciences, 2022)
Formaldehyde has been widely observed in the icy mantle of interstellar grains. H2CO may be formed from successive hydrogenations of CO and may further contribute to the chemical complexity of the Interstellar medium (ISM) participating to heterogeneous reactions with colliding gas phase atoms. Within this context, Eley-Rideal and Langmuir-Hinshelwood rate constants of H2 formation on a formaldehyde doped amorphous water ice grain model of the ISM, were computed over a wide temperature range [15–2000 K]. We used classical molecular dynamics (MD) simulations to build the model of the H2CO doped ice surface. Then we studied theoretically by means of hybrid QM/MM ab initio and molecular mechanics methodology (ONIOM) H atoms abstraction from formaldehyde molecules and the H2 formation. Specifically, we investigate the reactivity of the gas phase H atom toward one formaldehyde molecule lying at one of the slab surfaces. The reaction path and the energetics are predicted, the mechanism is found to be exothermic by 14.89 kcal/mol and the barrier is 6.75 kcal/mol at the QM level CBS/DLPNO-CCSD(T)//ONIOM/aug-cc-pVTZ. We employ two approaches that take into account tunnelling and non-classical reflection effects by means of the Zero Curvature Tunnelling (ZCT), and the Small Curvature Tunnelling (SCT) which all provided comparable results to predict the kinetics of the reaction path. The rate constants show important quantum tunnelling effects at low temperatures when compared to rates obtained from the purely classical transition-state theory (TST) and from the canonical variational transition state theory (CVT). Corner cutting effects are highlighted in the SCT calculations by 4 to 5 orders of magnitude with respect to ZCT rate constants at low temperatures.